2001
DOI: 10.1517/14622416.2.1.51
|View full text |Cite
|
Sign up to set email alerts
|

ABC drug transporters: hereditary polymorphisms and pharmacological impact in MDR1, MRP1 and MRP2

Abstract: Transport by ATP-dependent efflux pumps, such as P-glycoprotein (PGP) and multi-drug resistance related proteins (MRPs), influences bioavailability and disposition of drugs. These efflux pumps serve as defence mechanisms and determine bioavailability and CNS concentrations of many drugs. However, despite the fact that substantial data have been accumulated on the structure, function and pharmacological role of ABC transporters and even though modification of PGP function is an important mechanism of drug inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(69 citation statements)
references
References 103 publications
1
64
0
4
Order By: Relevance
“…However, these studies indicate that common polymorphisms that affect P-gp do not have global effects on its pump function. Taken together with the recent work of Hoffmeyer et al (2000) and Kerb et al (2001), polymorphisms that are linked to alterations in P-gp expression are more likely to be clinically significant than those studied here, which change coding sequence.…”
Section: Characterization Of Polymorphisms In the Human Mdr1 Genesupporting
confidence: 56%
See 1 more Smart Citation
“…However, these studies indicate that common polymorphisms that affect P-gp do not have global effects on its pump function. Taken together with the recent work of Hoffmeyer et al (2000) and Kerb et al (2001), polymorphisms that are linked to alterations in P-gp expression are more likely to be clinically significant than those studied here, which change coding sequence.…”
Section: Characterization Of Polymorphisms In the Human Mdr1 Genesupporting
confidence: 56%
“…Several recent reports indicate that polymorphisms are relatively common in the human MDR1 gene (Yoshimoto et al, 1988;Mickley et al, 1998;Decleves et al, 2000;Hoffmeyer et al, 2000;Liu and Hu 2000;Ameyaw et al, 2001;Brinkmann et al, 2001;Cascorbi et al, 2001;Hitzl et al, 2001;Ito et al, 2001;Kerb et al, 2001;Kim et al, 2001;Schaeffeler et al, 2001). This finding has stimulated interest in whether common coding polymorphisms affect function of P-gp and/or whether polymorphic variants are linked to altered drug pharmacokinetics.…”
mentioning
confidence: 99%
“…66 In addition to intrinsic or acquired overexpression of multidrug transporters in the BBB of patients with epilepsy, functional polymorphisms of these transporters may play a role in pharmacoresistance. 75,76 Furthermore, both overexpression and functional polymorphisms of multidrug transporters in patients with intractable epilepsy need not necessarily be restricted to the brain, but could also occur in other tissues, such as the small intestine, where PGP is thought to form a barrier against entrance of drugs from the interstinal lumen into the bloodstream, thereby limiting their oral bioavailability. 4 In this respect, it is interesting to note that Lazarowski et al 77 have reported persistent subtherapeutic plasma levels of AEDs (including phenytoin and phenobarbital) despite aggressive and continuous AED administration in a patient with refractory epilepsy associated with overexpression of MDR1.…”
Section: Role Of the Bbb Abc Transporters In Drug Resistancementioning
confidence: 99%
“…Phase II metabolizing or conjugating enzymes consist of many superfamilies of enzymes mainly including sulfotransferases (SULT) [3], UDPglucuronosyltransferases (UGT) [4], and glutathione transferases [5]. Efflux transporters, including p-glycoprotein (p-gp) [6], multidrug resistance associated proteins (MRPs) [6], and organic anion transporter (OAT) [7] are expressed in many tissues such as the liver, intestine, kidney and brain, where they present a formidable barrier to drug penetration, and play crucial roles in drug absorption, distribution and excretion [6,8,9]. Drugs that undergo extensive phase I metabolism, phase II conjugation and/or efflux by various transporters have poor bioavailability and are more prone to metabolism-based drug interactions.…”
Section: Introductionmentioning
confidence: 99%